Comparative simulation and experimental investigations on Ba1-xCaxTiO3 perovskites for optical and thermoelectric applications - Muhammad Tauseef Qureshi; Umer Farooq; Mahmoud Al Elaimi; Hira Affan; Ghazala Yunus; Abdul Moiz Mohammed; Maria Khalil; Murtaza Saleem (Results in Physics)
This study explores the various properties of CaxBa1-xTiO3 perovskites, focusing on its electronic, optical, and thermoelectric response through density functional theory and experimental methods. The findings reveal that Ca containing BaTiO3 compositions exhibit enhanced optical parameters, which makes these strong choice for optoelectronic devices. The density of states demonstrates substantial contributions of O-p states in the valence band and the Ti-d state within conduction band, forming a p-d hybridization that is crucial to the material’s electronic structure. The thermoelectric properties improve with Ca content, demonstrating a higher Seebeck coefficient and improved thermoelectric figure of merit, despite lower electrical conductivity. X-ray diffraction analysis confirms a phase pure cubic crystal structure. Optical analysis shows improved refractive index, absorption, and conductivity. The study reports the decrease in band gap from 2.96 eV for pure BaTiO3 to 2.5 eV for a maximum Ca containing composition. The results indicate that Ca incorporated BaTiO3 could be utilized as a potential material for optical, as well as thermoelectric applications.